基于语料库的新加坡华语量词系统 = Classifiers in Singapore Mandarin Chinese : a corpus-based study - 袁雪莲 Yuan, Xuelian (2016)
新加坡华语是现代标准汉语的域外变体之一，它基本上是以现代汉语普通话为基础，因此与普通话大体上是一致的。然而，新加坡华语因受到社会背景、历史 发展和语言环境的影响（李临定、周清海 2002；陆俭明等 2002），在许多方面都 与普通话有区别之处，而量词是其中的一方面。目前为止，学术界上有关新加坡华语量词的研究都主要着重于论述新加坡华语量词的特殊用法，而并未系统整理新加坡华语中的量词。因此，本文旨在基于大型的语料库（包括书面语语料和口语语料）对新加坡华语中的量词进行统计、归纳、考察及分析。本文是第一个基于大型语料库对新加坡华语量词的一个系统考察，并比较新加坡华语书面语与口语的异同之处，以及新加坡华语与普通话两个量词系统的差异。同时，本文也以网络搜索和问卷调查的形式，考察新加坡华语特殊的“形容 词+量词”结构。总体而言，通过对新加坡华语中的量词进行全面系统性的梳理和考察，本文 发现新加坡华语书面语与口语的差异主要集中在固定量词和个体量词这两个量词类别上，而新加坡华语与普通话的差异主要集中在量度词的范围,尤其是固定量词的类别上。此外，本文也发现能够进入新加坡华语特殊“形容词+量词”结构的形容 词和量词及其类别。Singapore Mandarin Chinese (SMC) is a variety of the Modern Standard Chinese. Thus, SMC is generally similar to other varieties of Mandarin Chinese such as Mainland Mandarin Chinese (MMC) in terms of phonology, vocabulary and grammar. However, due to a variety of factors, such as the influence of her societal background,historical development and language environment (Li, Zhou, 2002; Lu, 2002), there are key differences between SMC and other varieties of Mandarin Chinese. These differences encompass aspects including the usage of classifiers. Previous studies have been carried out to investigate the differences in terms of grammatical use between SMC and the other varieties of Mandarin Chinese – particularly on the usage of classifiers. However, these studies focused largely on classifiers that are unique to SMC. Studies have yet to be conducted on the classifier system in SMC. With large data from the corpus of SMC (both written and spoken), this study aims to carry out a comprehensive and systematic investigation of the classifiers in SMC, and thereafter compare the classifiers between the written and spoken form, SMC and MMC. In addition, a combination of survey questionnaires and internet searches were carried out to investigate the “adjective+classifier” (adj+CL) phrase structure that is unique to SMC. In summary, through thorough investigation and analysis of the classifiers in SMC, this study identified that the key differences between the written and spoken SMC to be in classifier types – standard measure words and individual classifiiers. Classifiers in SMC and MMC also differ mainly in the category of measure words,in particular, standard measure words. Furthermore, this study has also ascertained the types of adjectives and classifiers which can be used in the “adj+CL” phrase structure.